Visual Tools for Food Safety Assesment of Biotechnological Products - Cando Díaz, Manuel Ignacio; Romero Vásquez, Katherine Lissette; Cortez Tunja, Daniel Adrián; Amaya Villagran, Braden Anthony (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Visual tools in food safety assessment with nutrition labeling are a crucial approach to facilitate consumers' understanding of nutrition information. These tools include labeling systems such as the nutrition traffic light or warning front labels, as well as mobile applications and interactive websites. They aim to simplify the interpretation of nutrition information and help consumers make healthier food choices. In various contexts, such as Ecuador, these visual tools play a vital role in improving the accessibility and usefulness of nutrition labeling, helping to promote healthier eating and prevent diet-related diseases. Their effective implementation and their impact on public health continue to be areas of evolving research and development